The hair tales of women of color in Northern Manhattan: a qualitative analysis - Vilfranc, Chrystelle L.; Houghton, Lauren C.; Tsui, Felice; Barrett, Emily; Llanos, Adana A. M.; Pennell, Kurt; Walker, Desiree A. H.; Martinez, Micaela; Morton, Beaumont; Shepard, Peggy; Terry, Mary Beth; McDonald, Jasmine A. (Frontiers in Reproductive Health, 2024)
Introduction Exposure to endocrine disrupting chemicals (EDCs), such as phthalates, can negatively impact maternal and child health, contributing to impaired fetal growth, preterm birth, and pregnancy complications, as well as increased downstream risks of cardiometabolic disease and breast cancer. Notably, women of color (WOC) are the largest consumers of personal care products, which are a common source of EDC exposure. Methods The Let's Reclaim Our Ancestral Roots (Let's R.O.A.R) Pilot Study developed an educational intervention delivered during pregnancy to promote reduced use of phthalate-containing hair care products (HCPs). This mixed-methods study included: (1) a quantitative analysis and (2) a qualitative analysis of the educational sessions and the semi-structured focus groups to evaluate the factors that influenced the hair care practices and product choices of WOC at various stages of life, including their current pregnancy (hereafter referred to as the hair journey). During the sessions, participants learned about EDCs (with a focus on phthalates), the unequal burden of exposure for WOC, adverse implications of exposure, and exposure reduction strategies. Focus group sessions provided insight into participants' hair journeys from childhood to the current pregnancy and explored factors during their hair product selection process. All sessions were transcribed and imported into NVivo Version 12 for coding and thematic analysis. Results A total of 46 individuals were enrolled in the study, and 31 participated in an educational session. This current work synthesizes the qualitative analysis of this study. We identified two important life stages (before and after gaining agency over hair care practices and product choices) and three dominant themes related to HCP use: (1) products that impacted the hair journey, which involved all mentions of hair products, (2) factors that influenced the hair journey, which included individuals or entities that shaped participants' hair experiences, and (3) the relationship between hair and sense of self, where sense of self was defined as the alignment of one's inner and outer beauty. Conclusion The themes intersected and impacted the participants' hair journey. Cultural integration was a sub-theme that overlapped within the dominant themes and participants discussed the effect of traditions on their hair experiences.